Implementation of the BUMA School industrial class at State Vocational High School 2 Cilacap in collaboration with PT Bukit Makmur Mandiri Utama - Darwanto Darwanto; Edhy Susatya; Muchlas Muchlas (Privietlab, 2026)
This study analyzes the implementation of the BUMA School industrial class at State Vocational High School 2 Cilacap in collaboration with PT Bukit Makmur Mandiri Utama (BUMA). Using school–industry partnership, link and match, and the CIPP evaluation model (context, input, process, and product), it explains how and why the program operates. A qualitative case study design was employed. Data were collected through semi-structured interviews, observations of the school environment and workshops, and program documents. The informants included one PT BUMA representative, one school representative, five alumni, and two BUMA School students. Data were analyzed through deductive coding based on CIPP components and inductive coding of emerging themes, with validity ensured through source and technique triangulation. The context findings show that the program responded to PT BUMA’s demand for heavy-equipment operators and mechanics, the vocational education revitalization agenda, and corporate social responsibility commitments. Inputs included an MoU, curriculum synchronization, teacher internships, guest instructors, facilities, financing, and coordination forums among the partner schools. The process comprised pre-implementation, implementation, and post-implementation stages, including student selection, the Basic Mechanics Course, mental and physical development, industrial work practice, certification, medical examinations, employment contracts, advanced training, and alumni tracking. The product component showed continuity across seven cohorts involving 208 participants, strengthened basic heavy equipment competencies, improved discipline and work readiness, and enhanced school and corporate image. However, evidence of program effectiveness should be strengthened through quantitative indicators, including certification pass rates, graduate recruitment rates, job retention rates, and employer satisfaction levels. Major constraints include coordination problems, limited LMS access and Internet quotas, inadequate workshop facilities, the absence of a heavy-equipment specialization, dependence on a single company, and unequal distribution of program benefits across participating students, alumni, and partner schools.